DEVELOPMENT AND VALIDATION OF A CROSS-CULTURAL EORTC MEASURE OF SPIRITUAL WELLBEING (SWB) FOR PALLIATIVE CARE PATIENTS WITH CANCER. Issue 1 (1st March 2014) - Vivat, B; Young, T; Winstanley, J; Arraras, JI; Bennett, MI; Brédart, A; Costantini, A; Fisher, SE; Greimel, E; Guo, J; Irarrazaval, ME; Kobayashi, K; et al.
Abstract : Introduction: Spiritual care and spiritual wellbeing (SWB) are central to palliative care, but no measures of SWB have yet been developed cross-culturally. Aim(s) and method(s): In 2002 the EORTC Quality of Life (QL) Group began international development of an SWB measure for palliative patients. Three domains of SWB were initially hypothesised, and items developed accordingly. Data for Phase IV field-testing and validation of the measure were collected from January 2012 to July 2013. Participants completed the 36-item provisional SWB measure and a structured debriefing interview. EORTC QLQ-C15-PAL, socio-demographic and clinical data were also collected, and a sub-set of test-retest data. The scale structure was assessed using Principal Component Analysis (PCA) and Rasch analysis and further validity explored using known group comparisons. Results: 458 patients from 14 countries took part; 188 Christian, 50 Muslim, 23 Buddhist, and 158 with no religion. All items showed good score distribution. 275 patients (60%) found no items problematic, but small percentages indicated difficulties with 6 items. Combining patient feedback with PCA and Rasch analysis led to deletion of a few items. Four distinct domains explain 53% of the variance. No remarkable differential item functioning (DIF) was found for age, sex, geographical region or belief in God. Goodness of fit measures were within guidelines. Global SWB correlated weakly with global QL. Conclusion(s): This EORTC measure of SWB is available for use in palliative care research and practice, and has both measurement and intervention characteristics. Future studies will specifically recruit people in minority religious and/or ethnic communities under-represented in this already diverse sample.